2023
DOI: 10.3390/sym15071300
|View full text |Cite
|
Sign up to set email alerts
|

Development of Fixed Point Results for αΓ-F-Fuzzy Contraction Mappings with Applications

Abstract: This manuscript contains several fixed point results for αΓ-F-fuzzy contractive mappings in the framework of orthogonal fuzzy metric spaces. The symmetric property guarantees that the distance function is consistent and does not favour any one direction in orthogonal fuzzy metric spaces. No matter how the points are arranged, it enables a fair assessment of the separations between all of them. In fixed point results, the symmetry condition is preserved for several types of contractive self-mappings. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Even in the present time, for the benefit of human beings, researchers of several fields including computers, physics, applied mathematics, and many others are benefiting from using the Banach contraction principle. Sessa et al [3] demonstrated some FP results and provided an application for nonlinear differential equation. In 1968, Kannan [4] gave some FP results and enhanced the era of fixed point theory.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the present time, for the benefit of human beings, researchers of several fields including computers, physics, applied mathematics, and many others are benefiting from using the Banach contraction principle. Sessa et al [3] demonstrated some FP results and provided an application for nonlinear differential equation. In 1968, Kannan [4] gave some FP results and enhanced the era of fixed point theory.…”
Section: Introductionmentioning
confidence: 99%